2011
DOI: 10.2527/jas.2010-3079
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies for feedlot and growth traits in cattle1

Abstract: ABSTRACT:A genome wide-association study for production traits in cattle was carried out using genotype data from the 10K Affymetrix (Santa Clara, CA) and the 50K Illumina (San Diego, CA) SNP chips. The results for residual feed intake (RFI), BW, and hip height in 3 beef breed types (Bos indicus, Bos taurus, and B. indicus × B. taurus), and for stature in dairy cattle, are presented. The aims were to discover SNP associated with all traits studied, but especially RFI, and further to test the consistency of SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 21 publications
12
120
2
4
Order By: Relevance
“…The MVP for RFI was not related to RFI or FCR in the Brahman cattle in this experiment (Table 11). This is consistent with failure of feed efficiency markers to validate across different cattle breeds (Johnston and Graser, 2010;Bolormaa et al, 2011a;Littlejohn et al, 2012), with the RFI MVP explaining only 1% of phenotypic variation in RFI in purebred Bos indicus cattle and less than 1% of phenotypic variation in Bos taurus and Bos indicus × Bos taurus crossbred cattle (Johnston and Graser, 2009). This is despite reports of multiple markers explaining a large proportion of genetic variation in several other studies (Moore et al, 2009).…”
Section: Association Among Mvp and All Phenotypic Traitsmentioning
confidence: 70%
See 1 more Smart Citation
“…The MVP for RFI was not related to RFI or FCR in the Brahman cattle in this experiment (Table 11). This is consistent with failure of feed efficiency markers to validate across different cattle breeds (Johnston and Graser, 2010;Bolormaa et al, 2011a;Littlejohn et al, 2012), with the RFI MVP explaining only 1% of phenotypic variation in RFI in purebred Bos indicus cattle and less than 1% of phenotypic variation in Bos taurus and Bos indicus × Bos taurus crossbred cattle (Johnston and Graser, 2009). This is despite reports of multiple markers explaining a large proportion of genetic variation in several other studies (Moore et al, 2009).…”
Section: Association Among Mvp and All Phenotypic Traitsmentioning
confidence: 70%
“…The development of improved MVP for feed efficiency and other traits will require large-scale discovery and validation of SNP from genome-wide association studies (Bolormaa et al, 2011a(Bolormaa et al, , 2011b(Bolormaa et al, , 2013Eggen, 2012) and SNP panels, which are becoming increasingly available commercially, with more gene markers contributing to genotypic and phenotypic variation. Their utility would be enhanced by the development of phenotyping systems with more efficient, higher throughput and standardized phenotyping, particularly for difficult to measure traits, such as cooked beef palatability and FCR, that allow for deeper biological phenotyping, enabling meaningful biological phenotypes to contribute to commercial traits (Hocquette et al, 2012;Pollak et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Association studies in livestock generally have small sample sizes (approximately 2,000 records), and hence relatively high false discovery rates compared with GWASs in humans (for example, [30]). This means that defining genes identified by livestock GWASs is more uncertain than those identified in humans.…”
Section: Variants With Small Effectsmentioning
confidence: 99%
“…Spacing of the 50K is sufficient to locate SNP that are in linkage disequilibrium (LD) with underlying QTL within cattle breeds, but inconsistent LD patterns among cattle breeds (Gautier et al, 2007;Bovine HapMap Consortium, 2009) indicate that, across breeds, the same SNP from the 50K will not consistently be associated with the same underlying QTL. A comparison of 50K SNP effects on feed intake and efficiency estimated in Australian and US cattle showed that individual SNP effects were inconsistent but identified 1-Mb intervals containing SNP associated with the traits in each population (Bolormaa et al, 2011;Pollak et al, 2012). Higher marker density within these intervals might identify SNP having more consistent associations across populations of cattle due to stronger, more consistent LD between QTL and SNP with closer spacing between SNP.…”
Section: Low-cost Genotypingmentioning
confidence: 99%